Удосконалення механізму реалізації ендогенного потенціалу інноваційного розвитку національної економіки - Гуменюк, О. С.; Gumeniuk, Oleksandra (КНТУ, 2014)
У статті проаналізовано загальні тенденції дії господарського механізму реалізації ендогенного потенціалу інноваційного розвитку. Він представлений як цілісна система народного господарства і повинен формуватись інституційним, фінансовим, управлінсько-кадровим, ресурсним та матеріально- технічним забезпеченням, включає реалізацію організаційно-управлінського потенціалу, а також процеси мобілізації внутрішніх можливостей та ресурсів, для спрямування їх на інноваційні цілі з наступним нагромадженням і відтворенням. The article analyzes the general trends of the economic mechanism of the endogenous potential implementation of the national economy innovative development. It is represented as a complete system of the economy and has formed the institutional, financial, administrative and personnel, resources and logistics, including the implementation of organizational and management capacity, and the processes of mobilization of internal capabilities and resources to guide them on innovative targets with subsequent accumulation and reproduction. Оutlines the organizational and economic mechanism as part of the mechanism of the innovation development, including the appropriate procedure for planning, financing, logistics, special structures appropriate channels to obtain information, assess of economic efficiency and other components. Presents components of endogenous potential that includ market, natural resources, intellectual and labor, organizational and administrative, financial, innovation potential and article outlines its internal capabilities, resources. Shows their focus on innovative targets for mobilization and subsequent accumulation and reproduction. Mobilization could be based on existing resource capabilities and ensure their growth through the effects of cumulative causation positive experience productive orientation using them to achieve the strategic goals of innovation. System of government and subordinate structures should generate and implement innovative policies, regulatory framework, intellectual property rights, innovation and business financing. Reforming the system of public administration, such as the simplification of bureaucratic procedures and gain control over the activities of subordinate services and departments will promote innovation.
Improving the mechanism of the endogenous potential implementation of the national economy innovative development
Keywords: ендогенний потенціал; механізм реалізації інноваційного розвитку; мобілізація внутрішніх можливостей та ресурсів; endogenous potential; mechanism for the implementation of innovative development; mobilization of internal resources and capabilities